2020
DOI: 10.1002/mbo3.1018
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of stool microbiome methods for DNA yields and sequencing among infants and young children

Abstract: With the emergence of large‐scale epidemiologic human microbiome studies, there is a need to understand the reproducibility of microbial DNA sequencing and the impact of specimen collection and processing methods on measures of microbial community composition and structure, with reproducibility studies in infants and young children particularly lacking. Here, we examined batch‐to‐batch variability and reliability of collection, handling, and processing protocols, testing replicate stool samples from infants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Currently, there is no consensus regarding best practices for human stool collection and analysis, leading to concerns regarding the reliability and reproducibility of these datasets. Several factors including DNA extraction methods, sequencing technologies, and analytical approaches are known to have a significant impact on the characterization of the stool microbiota ( Lauber et al., 2010 ; Carroll et al., 2012 ; Goodrich et al., 2014 ; Sinha et al., 2015 ; Chiu and Chao, 2016 ; Sinha et al., 2017 ; Vogtmann et al., 2017 ; Antosca et al., 2020 ; Bartolomaeus et al., 2020 ), underscoring the importance of using standardized protocols to minimize bias.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus regarding best practices for human stool collection and analysis, leading to concerns regarding the reliability and reproducibility of these datasets. Several factors including DNA extraction methods, sequencing technologies, and analytical approaches are known to have a significant impact on the characterization of the stool microbiota ( Lauber et al., 2010 ; Carroll et al., 2012 ; Goodrich et al., 2014 ; Sinha et al., 2015 ; Chiu and Chao, 2016 ; Sinha et al., 2017 ; Vogtmann et al., 2017 ; Antosca et al., 2020 ; Bartolomaeus et al., 2020 ), underscoring the importance of using standardized protocols to minimize bias.…”
Section: Introductionmentioning
confidence: 99%
“… 31 and Antosca et al . 32 . We also found that mouse fecal samples collected, sequenced and analyzed 3 years apart had very similar microbiota compositions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequencing platforms including the Illumina MiSeq we used has sequencing errors, and separate sequencing runs may contribute to differences in the gut microbiota compositions. However, the reproducibility of Illumina MiSeq sequencing for microbiota analysis have been evaluated and high reproducibility was shown by Caporaso et al 29 , Eriksson et al 30 , Teng et al 31 and Antosca et al 32 . We also found that mouse fecal samples collected, sequenced and analyzed 3 years apart had very similar microbiota compositions (Fig.…”
mentioning
confidence: 99%
“…Furthermore, SRS-2 scores have high consistency over time, minimizing the effect of age at which the surveys were administered in the two cohorts [ 57 ]. Another limitation is the variation in stool sample collection methods between the two studies, including the timing of sample collection, which may have led to differential detection of certain species; much of the concern about collection and processing methods may be alleviated with a rigorous comparison study of methods identifying data alignment with variable methods [ 58 ].…”
Section: Limitationsmentioning
confidence: 99%